Molecular phylogenetics of pangasiids in Peninsular Malaysia using mitochondrial and nuclear genes - Mattar, Azlina Zainab (2012)
Pangasiidae is a large family of freshwater catfishes found throughout South and Southeast Asia. Typically, Pangasiidae are characterized by having smooth skin, two pairs of relatively short barbels and a subterminal mouth, a dorsal fin with a strong spine, small adipose fin, and a forked caudal fin which is separated from the anal fin. Some indigenous pangasiids, such as Patin Buah (Pangasius nasutus) and Patin Muncung (Helicophagus waandersii) are highly valuable and popular freshwater fish in Pahang and Perak. Unfortunately, currently, these fishes have become threatened species in rivers. Some introduced species of pangasiids from Thailand, such as P.hypophthalmus, has become one of the important freshwater fish for culture in Malaysia as a food source. Thus, it is vital to study the genetic relationships among various species of pangasiids in Malaysia. The aim of this study was to estimate phylogenetic relationships among species of the family Pangasiidae using both mitochondrial DNA (cytochrome c oxidase subunit 1 (COI), cytochrome b (Cyt b) and 16S rRNA (16S) and nuclear genes (RAG1 and RAG2). The locus effectiveness in reveals phylogenetic relationtionships among species of the family Pangasiidae was also determined. A total of 42 samples of fish species belonging to family Pangasiidae were collected from Perak, Selangor and Sungai Pahang and fish farm. DNA from individual sample were extracted from muscle tissue and purified for the analysis. The methods used to infer the phylogeny of this family were neighbour joining (NJ), maximum parsimony (MP), maximum likelihood (ML) and Bayesian analyses using MEGA4, PAUP and Mr. Bayes softwares. The Modeltest 3.7 was used to find the best model for ML and Bayesian analyses. The equences were used and aligned together with an outgroup of Ictalurus punctatus sequences recovered from GeneBank. In this study, 462 bp, 903 bp, 543 bp, 949 bp and 877 bp were successfully sequenced from COI, Cyt b, 16S, RAG1 and RAG2 genes, respectively. The results from all the phylogenetic analyses showed similar patterns. The genetic distance values between pangasiid species based on COI, Cyt b and 16S ranged from 0.015 to 0.170 while the genetic distance values recovered from RAG1 and RAG2 ranged from 0.008 to 0.046. The trees of NJ, MP, Bayesian and ML based on mitochondrial DNA and nuclear genes produced similar topologies. The pangasiids were divided into two clades (Clade 1 and Clade 2), in which Clade 1 consisted of P. nasutus, P. bocourti, P. micronemus and H. waandersii while Clade 2 comprised only P. hypophthalmus. This showed, H. waandersii was found to be closer to P. nasutus, P. bocourti, P. micronemus than to P. hypophthalmus, eventhough it belongs to different genus. This showed that P. nasutus, P. bocourti, P. micronemus and H. waandersii were monophyletic with significant values of more than 0.97 for Bayesian probability. The results clearly showed that mitochondrial DNA and nuclear genes can be used to isolate the native species of Malaysian pangasiids, such as P. nasutus, P. micronemus, P. bocourti and H. waandersii from the introduced species of P. hypophthalmus. Similar results revealed by both mitochondrial DNA and nuclear genes suggesting that these genetic markers are suitable to study the phylogenetic relationships among the pangasiid species, although Cyt b was found to be more effective than other markers. The results also suggest that the taxonomy of H. waandersii should be revised in the future. In order to validate genetic relationships among different species of pangasiids, additional indigenous species with larger sample size should be included in future studies.